H2 pressure dependence in the homogeneously catalyzed Guerbet reaction of ethanol to butanol using Mn(I) and Ru(II) - Roca Jungfer, Maximilian; Schwarz, J. Luca; Rominger, Frank; Oeser, Thomas; Paciello, Rocco; Hashmi, A. Stephen K.; Schaub, Thomas (ChemCatChem, 2024)
The homogeneously catalyzed Guerbet upgrading of ethanol to butanol can be modulated by the application of partial H2 pressure before the reaction. Ruthenium(II) PNP pincer complexes with methylene-extended acridine-based ligands and singly-chelated ruthenium(II) complexes with PN ligands perform best at very low catalyst loadings and upon the application of catalyst-specific pre-reaction partial H2 pressure. The combination of ruthenium(II) PNP pincer complexes and manganese(I) pincer complexes with MACHO-type PNP ligands allows for even lower ruthenium loadings while retaining low base load and consumption, thus enabling high space-time yields, catalyst productivity and recyclability. Mechanistically, Mn is proposed to stabilize coordinatively unsaturated Ru species and allow coordination of ethoxide to Ru instead of attacking the electrophilic ligand backbone based on NMR spectroscopy and X-ray crystallography.
Online veröffentlicht: 1. Februar 2024
Gesehen am 18.02.2025
Im Titel ist "2" tiefgestellt